Natural Compounds as Modulators of Cell Cycle Arrest: Application for Anticancer Chemotherapies - Bailon-Moscoso, Natalia; Cevallos-Solorzano, Gabriela; Carlos Romero-Benavides, Juan; Isabel Ramirez Orellana, Maria (Current Genomics, 2017)
Natural compounds from various plants, microorganisms and marine species play an important role in the discovery novel components that can be successfully used in numerous biomedical applications, including anticancer therapeutics. Since uncontrolled and rapid cell division is a hallmark of cancer, unraveling the molecular mechanisms underlying mitosis is key to understanding how various natural compounds might function as inhibitors of cell cycle progression. A number of natural compounds that inhibit the cell cycle arrest have proven effective for killing cancer cells in vitro, in vivo and in clinical settings. Significant advances that have been recently made in the understanding of molecular mechanisms underlying the cell cycle regulation using the chemotherapeutic agents is of great importance for improving the efficacy of targeted therapeutics and overcoming resistance to anticancer drugs, especially of natural origin, which inhibit the activities of cyclins and cyclin-dependent kinases, as well as other proteins and enzymes involved in proper regulation of cell cycle leading to controlled cell proliferation.
Keywords: Cell cycle arrest